Reduced order modeling of soft-body impact on glass panels. (1st April 2022) - Andersson, Linus; Kozłowski, Marcin; Persson, Peter; Austrell, Per-Erik; Persson, Kent
Abstract: In the paper, strategies for reduced order modeling of glass panels subjected to soft-body impact are developed by means of dynamic substructuring. The aim is to obtain accurate and computationally efficient models for prediction of the pre-failure elastic response. More specifically, a reduction basis for the subsystem representing the glass panel is established using correction modes, being fixed-interface component modes that considers loading on the substructure boundary. The soft-body impactor is effectively modeled by a nonlinear single-degree-of-freedom system, calibrated by experimental data. Furthermore, a simplified and computationally efficient modeling approach is proposed for the contact interaction between the glass panel and the impact body. An experimental campaign was carried out to validate the developed models. In particular, the glass strain was measured on simply supported monolithic glass panels subjected to soft-body impact. Additional impact tests were performed to determine the dynamic characteristics of the impactor. Moreover, a detailed numerical reference model was developed to evaluate the discrepancy between the experimental tests and the results provided by the reduced order models. The developed models show good agreement with the experimental results. For the studied load cases, it is shown that an accurate prediction of the pre-failure glass strain can be obtained by systems including only a few generalized degrees-of-freedom. Highlights: Reduced modeling of soft-body impact on glass panels using dynamic substructuring. Nonlinear SDOF model proposed for modeling the EN 12600 standardized impactor. Experimental methodology for estimating the impactor damping presented. Validation of reduced models by detailed finite element model and experimental data. Efficient and accurate models for predicting pre-failure elastic response developed.